Supremasi Hukum Dalam Kepemimpinan Berbasis Hindu - I Made Dwija Suastana (Kertha Wicaksana, 2022)
Leadership can be defined as the ability to coordinate and mobilize people or groups of people to achieve desired goals. Leadership is an activity to influence the behavior of others or the art of influencing human behavior, both individuals and groups. Discussions about leaders and leadership in general explain how to become a good leader, styles and traits that are in accordance with leadership and the requirements that an ideal leader needs to have. To measure the compliance of leaders or technocrats to the law, it can be seen from the real actions that have been taken. Especially those related to the substance of the law or legal products, both written and unwritten, as well as decisions from the judiciary. Comparative references can be obtained from written sources in the form of sacred literature, lontars about Hindu-based law and leadership and local wisdom, especially in Bali. The implementation of leadership that refers to Hindu law and literature has been carried out by Hindu technocrats who are involved in various sectors of life. Comparison of the experiences of these technocrats has an important role in enriching and renewing perspectives and leadership strategies that complement each other. It is hoped that a new paradigm can be formed that remains guided by positive law, Hindu literary sources and Balinese local wisdom.